2002
DOI: 10.1002/jctb.570
|View full text |Cite
|
Sign up to set email alerts
|

Production and recovery of poly‐3‐hydroxybutyrate from Methylobacterium sp V49

Abstract: Bacterial polyesters have shown potential as biodegradable plastics. Microorganisms capable of producing these polyesters from cheaper carbon sources and methods for their ef®cient recovery are widely studied worldwide. Methylobacterium sp V49, an environmental isolate, was cultivated on a mineral salts medium containing different carbon sources. Maximum accumulation of poly-3-hydroxybutyrate (PHB) within the bacterial cell was observed with glucose as the carbon source. Methanol and sugars such as sucrose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The methods of cell disruption can be divided into chemical (by using hypochlorite, acids, alkalis, or surfactants),74–76 enzymatic,77 and mechanical processes 78. All of these methods were developed with the purpose to dissolve or destroy the nonpolymeric cell materials (NPCMs).…”
Section: Polymer Recovery and Characterizationmentioning
confidence: 99%
“…The methods of cell disruption can be divided into chemical (by using hypochlorite, acids, alkalis, or surfactants),74–76 enzymatic,77 and mechanical processes 78. All of these methods were developed with the purpose to dissolve or destroy the nonpolymeric cell materials (NPCMs).…”
Section: Polymer Recovery and Characterizationmentioning
confidence: 99%
“…Several NPCM solubilizing approaches based on chemicals (sodium hypochlorite) [20]; surfactants (sodium dodecyl sulphate (SDS), palmitoyl carnitine) [9], [37]; surfactant-chelate combination (Triton X-100 and betaine with EDTA) [8], [35]; enzymatic (commercial enzymes such as bromelain, pancreatin; microbial Cytophaga and Microbiospora sp. lysing enzymes [23], [31], [35]; ionic liquids [13]; supercritical fluids [11], [24]; γ-irradation [12]; mechanical aids [12], [17], [25], [54]; dissolved air flotation [56]; osmotic cell fragility [16], [48]; spontaneous liberation [30] etc. to name a few have been reported for PHA recovery from NPCM [34].…”
Section: Introductionmentioning
confidence: 99%
“…Other bacterial genera ( Methylobacterium, Pelomonas , and Sphingomonas ) had high relative abundances on fresh tea leaves, which greatly decreased during the Fu Brick manufacturing process. Methylobacterium is known for the production of poly-β-hydroxybutyrate (Bourque et al, 1992 ; Yellore et al, 2000 ; Ghatnekar et al, 2002 ) and was identified as one of the core bacteria during the pile fermentation processing stage (Liu et al, 2019 ). It is also one of the predominant genera of raw Pu'er tea, which is another type of fermented tea derived from the leaves of C. sinensis var.…”
Section: Discussionmentioning
confidence: 99%